Um recurso lexicográfico baseado na semântica de frames no contexto do ensino bilíngue infantil - Oliveira, Lenir Marina Trindade de (Universidade do Vale do Rio dos Sinos, 2022)
This seeks to present a theoretical-methodological proposal at the interface between Cognitive Linguistics, more specifically from the perspective of Frame Semantics theory, and Pedagogical Lexicography, for the development of pedagogical lexicographical resources organized from the concept of semantic frame. We also aim to analyze what are the possible convergences between the theory of Frame Semantics and the science of Pedagogical Lexicography with regard to their premises and postulates; to determine the characteristics present in a model of pedagogical lexicographical resource organized from the concept of frame, discussing issues related to its structure and, finally, to present a model of linguistic description of frames and lexical units, taking into account the characteristics of the foreseen lexicographical resource , as a way of illustrating the proposal. The methodology of the work situates the environment and the subjects of our research; and based on the expertise of the SemanTec research group, it proposes the following steps as an analysis procedure: study of the domain to create a conceptual map, initial proposition of frames, survey of lexical units, presentation of the microstructure of frames and lexical units. Next, we proceed to the elaboration of a model version of the proposed lexicographical resource, where we discuss in detail each step foreseen for the creation of the product listed in the work methodology, presenting a conceptual map, the proposed frames and the relationships between them, the glosses, the lexical units lexica raised and the representation of each one. The research results show that the assumptions of Frame Semantics and Pedagogical Lexicography are similar because they constitute valuable tools for the creation of dictionaries, since both theories deal with a different conception for the organization of the lexicon. They pay attention to the importance of the context and the previous knowledge and experience of the speaker/consultant, and for contributing to an organization of meaning in a broader and more contextualized way, favoring a more effective experience of the speaker/consultant in relation to the use/understanding/acquisition of the language. When carrying out the methodological steps for the elaboration of the resource that we propose, we outlined the characteristics of our pedagogical lexicographical resource as a specialized product in the scope of the school routine of bilingual education, in the case of a bilingual resource, by bringing equivalents of glosses, frames and lexical units in Portuguese. We also bring the representation of lexical units through drawings made by children. We realized from the accomplishment of this research that the contribution of Frame Semantics to Pedagogical Lexicography is in the definition bias; more specifically in the way the lexicographical resource was produced, also considering its pedagogical proposal. This intersection of practices demonstrates how both the Frame Semantics theory and the science of Pedagogical Lexicography contributed to each other in the elaboration of the lexicographical resource model proposed here.
Keywords: Linguística cognitiva; Semântica de frames; Lexicografia pedagógica; Ensino bilíngue; Cognitive linguistics; Frame semantics; Pedagogical lexicography; Bilingual teaching; ACCNPQ::Lingüística, Letras e Artes::Lingüística